Experimental And Theoretical Performances Of A Solar Assisted Dehumidification Drying System For Heat Sensitive Products - Muhammad Yahya (ITP Press)
Problem statement: In most countries, conventional hot air drying method is commonly used for drying heat sensitive products. Although the method is simple and cheap, however the conventional hot air dryers are still not suitable to dry them because of resulting in low product quality. Approach: Solar assisted dehumidification drying system is suitable for drying ‘heat sensitive’ products like Centella Asiatica L because of drying process is conducted at low air temperature and low relative humidity. The main components of the drying system consist of a solar collector, an energy storage tank, an auxiliary heater, two blowers, two adsorber columns, two water-air heat exchanger, two water circulating pumps, a drying chamber and other ancillary equipment. A computer program was developed in MATLAB software to predict the performance of the drying system. The predicted results are compared with those obtained from experimental results. The performance is indicated by Pick up efficiency (?P), Coefficient of Performance (COP) and Solar Fraction (SF). Results: The maximum values of the pickup efficiency (?P ), solar fraction (SF) and coefficient of performance (COP), obtained from the predicted and measured data are as follows (93% and 97%), (0.34 and 0.3) and (69.3% and 70.5%), respectively with initial and final wet basis moisture content of Centella Asiatica L 88% and 15%, respectively at an air velocity is 3.25 m/s. Conclusion: Good agreement was found between predicted results and experimental results.